Association between age, sex and cervical and upper cervical rotation tests. Descriptive and correlational study in healthy volunteers - Carlos Zárate-Tejero; César Hidalgo-García; Orosia Lucha-López; Mar Hernández-Secorún; John Krauss; Pere Rodríguez-Rubio (SAGE Publishing, 2023)
Background: Active cervical spine rotation (ACROM Rot) shows cervical rotation and flexion rotation test (FRT); side-bending rotation test (SBRT) and upper cervical axial rotation test (C0-C2ART) are described to measure upper cervical rotation. The objectives of this study are (1) to describe the normal range of motion (ROM) of ACROM Rot, and the ROM in FRT, SBRT and C0-C2ART tests; (2) to explore the correlation among the four tests and (3) to investigate the influence of age and sex in their ROM. Methods: A cross-sectional study was carried out with healthy volunteers from 18 to 75 years of age. Tests were measured using a CROM device and a bubble inclinometer. Descriptive analysis was performed to establish normative data for the ROM tests. Correlation analysis was conducted to understand the relation between upper and global cervical rotation ROM and among the three upper cervical rotation tests. Linear regression models were developed to understand the influence of age and sex in the ROM of all tests. Results: Normative values were obtained from 122 healthy volunteers (50% male), by sex and age strata. The degree of correlation ranged between 0.582 ( p  < 0.01) for FRT and ACROM Rot left and 0.217 ( p  < 0.05) for SBRT and C0-C2ART left. Linear regression models showed the influence of sex for ACROM Rot right (men −4.64° less than women), SBRT (men −4.1° less than women) left and C0-C2ART right and left (men −2.24° and −1.78° less than women). The age influenced rotation ROM with a decrease for every 10 years of −2.11° and −1.96° for ACROM Rot right and left, of −1.72° and −1.26° for FRT right and left and −0.58° and −0.41° for C0-C2ART right and left in the linear regression models. No association was found between age and SBRT ( p  = 0.63 for right SBRT and p  = 0.49 for left SBRT). Conclusion: Weak-to-moderate correlation was found between the upper cervical spine rotation tests and with the ACROM. Women had a larger ROM in ACROM Rot right, SBRT left and C0-C2ART. Decreases in ROM related with age were observed for ACROM Rot, FRT and C0-C2ART but not for SBRT.